2022
DOI: 10.1021/acs.energyfuels.2c01736
|View full text |Cite
|
Sign up to set email alerts
|

Wood Derived Fast Pyrolysis Bio-liquids as Co-feed in a Fluid Catalytic Cracking Pilot Plant: Effect of Hydrotreatment on Process Performance and Gasoline Quality

Abstract: Co-feeding biogenic feeds in fluid catalytic cracking (FCC) units benefits from exploiting existing refinery assets to produce biogenic fuels. It is the most cost-effective way to comply with step-by-step increasing the target of renewable energy in road and rail transport of the European Union. Fast pyrolysis bio-liquids derived from wood offer a unique opportunity to reach those targets without having to address the typical food vs fuel debate. In the present work bio-liquids derived from pinewood in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Lutz et al studied the effect of hydrotreatment on process performance and gasoline quality when wood-derived FPBOs are used as co-feed in an FCC pilot plant and concluded the potentiality of the co-FCC process as a possible near-future pathway to ensure high biofuel contents in commercially available fuels. Janosik et al presented an approach that involves complete dewatering of FPBO, followed by esterification.…”
Section: Co-refining Of Bioliquids and Fossil Oils In Refinery Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutz et al studied the effect of hydrotreatment on process performance and gasoline quality when wood-derived FPBOs are used as co-feed in an FCC pilot plant and concluded the potentiality of the co-FCC process as a possible near-future pathway to ensure high biofuel contents in commercially available fuels. Janosik et al presented an approach that involves complete dewatering of FPBO, followed by esterification.…”
Section: Co-refining Of Bioliquids and Fossil Oils In Refinery Processesmentioning
confidence: 99%
“…Both cracking and the capability to remove oxygen from the biocrude are required from these processing units, and therefore, co-processing could potentially take place in the fluid catalytic cracker (FCC), hydrotreater, or hydrocracker. Lutz et al 11 studied the effect of hydrotreatment on process performance and gasoline quality when wood-derived FPBOs are used as co-feed in an FCC pilot plant and concluded the potentiality of the co-FCC process as a possible near-future pathway to ensure high biofuel contents in commercially available fuels. Janosik et al 12 presented an approach that involves complete dewatering of FPBO, followed by esterification.…”
Section: ■ Co-refining Of Bioliquids and Fossil Oils In Refinery Proc...mentioning
confidence: 99%
“…Coprocessing of the FPBO in industrially available refinery processes, such as fluid catalytic cracking (FCC), is considered beneficial to produce high-value chemicals of gasoline, light olefins, and middle distillates, while part of their carbon is biogenic. The coprocessing of the FPBO in the FCC unit has been widely investigated considering different upgrading methods, such as catalytic upgrading and hydroprocessing, , FCC catalyst advancement, , as well as catalytic cracking condition optimization. The addition of pyrolysis bio-oil (up to 10 wt % feed share) was reported to provide successful processing with minor effect on the produced fuel quality. ,, One of the main reasons for upgrading the FPBO via a hydrotreatment process is to be able to introduce this valuable renewable product into the current refinery units and replace the fossil-based carbon resources with renewable ones.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrotreating the biocrude was noted to relieve catalyst deactivation during coprocessing by removing coke-forming species and metals like Fe and K. Pyrolysis bio-oils are much harder to process than HTL biocrudes because of their extreme oxygen content (up to 40 wt %) and low chemical stability. The benefits of hydrotreating pyrolysis bio-oil before coprocessing through FCC have been highlighted by various research groups. , It is generally concluded that hydrotreating pyrolysis bio-oil helps to reduce coke formation and deterioration of product selectivity. The coprocessing of hydrodeoxygenated pyrolysis bio-oil with straight-run gas oil in a hydrotreating process has also been investigated .…”
Section: Introductionmentioning
confidence: 99%